PENERAPAN METODE BELAJAR AKTIF TIPE GROUP TO GROUP EXCHANGE (GGE) UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR ALAT UKUR SISWAKELAS X SMK MUHAMMADIYAH 3 KLATEN UTARA TAHUN PELAJARAN 2014/2015 - Mursyid Zuny Aziz; Samsul Hadi (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to describe (1) learning creativity of measurement tool subject among the tenth grade students of SMK Muhammadiyah 3 Klaten Utara in the academic year 2014/2015 and (2) learning achievement of measurement tool subject among the tenth grade students of SMK Muhammadiyah 3 Klaten Utara in the academic year 2014/2015. This study was an action research. Techniques collecting data used test and documentation. This study shows that (1) the implementation of group to group exchange could improve learning creativity. The learning creativity of cycle was 45.23, while the learning creativity in cycle II was 45.23. (2) the implementation of group to group exchange could improve learning achievement of measurement tool subject among the tenth grade students of SMK Muhammadiyah 3 Klaten Utara in the academic year 2014/2015. There was improvement of scores in cycle I and cycle II. The average score in cycle I was 58.85, cycle II was 75.14. It could be stated that the implementation of group to group exchange to improve learning creativity and lerning achievement of measurement tool subject among the tenth grade students of SMK Muhammadiyah 3 Klaten Utara in the academic year 2014/2015.